Improving Elementary Students’ Conceptual Understanding of Energy Transformation through a PBL-Integrated with PhET Simulations, Songs, and Gamified Quizzes - Safitri, Riska Diana; Sutikno, Putri Yanuarita (Jurnal Pendidikan MIPA, 2025)
The abstract concept of energy transformation is a subject in the natural and social sciences that students frequently find difficult to comprehend. Conventional learning methods are less effective in enabling students to actively engage in the learning process and visualize energy transformation concepts. Consequently, students encounter challenges in comprehending the energy transformation process, the relationship between energy, and examples of objects. The goal of this study is to evaluate how effective problem-based learning, which includes PhET simulations, gamified quizzes, and songs, is in helping fourth-grade students at SD Negeri Losari better understand energy transformation concepts. The quasi-experimental method was employed in this study, with a nonequivalent control-group design. The experimental class IV A consisted of 21 students, while the control class IV B had 20 students. The total number of students in the sample was 41. The total sampling technique was employed in conjunction with nonprobability sampling. Teaching was conducted in the experimental class (IVA) through PhET simulation, gamification, problem-based learning, and melodies. In contrast, the control group (IV B) implemented conventional teaching methods in conjunction with instructional videos. The independent sample t-test and N-Gain test were the methods of statistical analysis. A significant improvement in learning outcomes was confirmed by the independent t-test, which yielded a p-value of less than 0.05. In contrast to the control class, which achieved an average N-Gain score of 0.2678 (low), the experiment class achieved an average N-Gain score of 0.6655 (moderate). This finding suggests that the conceptual comprehension of energy transformation is enhanced through the incorporation of gamified quizzes, songs, PhET simulations, and problem-based learning.    Keywords: PhET simulations, problem-based learning, song, quizzez, energy transformation.